Ghana’s Economic and Agricultural Transformation: Past Performance and Future Prospects - Ehui, Simeon K. (2019)
Simeon Ehui BOOK LAUNCH Ghana’s Economic and Agricultural Transformation: Past Performance and Future Prospects Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) OCT 9, 2019 - 12:15 PM TO 01:45 PM EDT